Pengaruh Komposisi Dewan Pengawas Syariah Terhadap Pengungkapan Tata Kelola Syariah - Devi Anisa Ramandani; Rita Wijayanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of the size, dual positions, educational qualifications, and education level of the Sharia Supervisory Board (SSB) on the disclosure of Sharia governance in Sharia commercial banks (BUS) during the period 2014-2023. The population in this study is Islamic Commercial Banks in Indonesia. While the sample in this study was determined using purposive sampling technique. data collection techniques using documentation using secondary data in the form of annual reports of Islamic commercial banks in 2014-2023. This test data analysis consists of classical assumption tests and multiple linear regression. This study contribute to the development of Sharia governance and this study is also expected to increase understanding of the role of Sharia Supervisory Boards (DPS) in ensuring compliance with principles in Islamic financial institutions.